Leadership Style of Student Production House Organization (Case Study on Label N) - Ichsan Adil Prayogi; Erika Yulianti (Jurnal Komunikasi, 2023)
The research is based on finding out how the leadership style of a production house founded by college students named Label N. This research uses a qualitative method with a case study approach. Qualitative research with a case study approach seeks to describe data in words or sentences separated by categories to obtain conclusions. Sources of data were collected through in-depth interviews regarding the leadership style applied by Label N. In the leadership style, Label N tries to establish a democratic leadership style. However, this democratic leadership style which is similar to the "four Likert system leadership style" in the fourth system, can run more smoothly if all members' views can be open in accepting each other's opinions so that when discussion no debate causes conflict. Members are also advised to keep the main focus in the discussion so as not to get out of the topic being discussed. In addition, because this leadership style is the “four Likert system leadership style" in the fourth system, we must be able to respect ideas that are data from other members, this is intended to keep things conducive to the ongoing discussions. This leadership style is also referred to as "participatory", as it allows active participation and contribution from all members in decision making